Association Between Hyponatremia and Maintenance Intravenous Solutions in Critically Ill Children: A Retrospective Observational Study - Fernández-Sarmiento, Jaime; Pérez, Andrea; Echeverri, Maria Alejandra; Jimenez, Paola; Joachim, Maria Alejandra; Andrés-Jagua, (Frontiers in Pediatrics, 2021)
Objetive: We sought to determine the association between maintenance intravenous solutions and the presence of hyponatremia in children in pediatric intensive care (PICU). Materials and methods: An analytical observational study in children hospitalized in the PICU between January 2015 and December 2018. Patients who received maintenance fluids within the first 48 hours after admission and who had at least two serum sodium levels drawn during this time were included. Measurements and Main Results: A total of 1,668 patients were admitted to the PICU during the study period, 503 of whom met the inclusion criteria. The median age was 24 months (IQR 8-96) and 50.9% were female. Altogether, 24.1% of the children developed hyponatremia; it was more frequent in those who received hypotonic solutions (63% vs 37%; OR 1.41 95% CI 0.92, 2.15 p=0.106), who also had a longer hospital stay (20 days vs. 14 days, difference in means 8 days, 95% CI 2.67, 13.3, p=0.001). Children who received loop diuretics and those who were postoperative had a greater risk of developing hyponatremia if they received hypotonic solutions (aOR 2.1 95% CI 1.41, 3.0, p=0.000). Those with balanced isotonic solutions had a lower risk of developing hyponatremia (aOR 0.59 95% CI 0.35, 0.99, p=0.004) and hyperchloremia (aOR 0.51 95% CI 0.34, 0.77, p=0.000), adjusted for disease severity. A greater risk of death was found in the group with severe hyponatremia < 130 mEq/L (aOR 9.75 95% CI 1.64 -58.15; p=0.01). Conclusions: Hyponatremia associated with the use of hypotonic maintenance solutions occurs in one out of four children in intensive care. The use of these solutions is associated with a longer hospital stay, and the main risk groups are postoperative patients and those who receive loop diuretics. Clinical studies are needed to determine which maintenance solutions have the greatest efficacy and safety in critically ill children. Key words: fluids, unbalanced solutions, balanced solutions, sodium, antidiuretic.